The Effect Of Work Life Balance, Work Motivation And Work Environment On Employee Performance With The Application Of Akhlak Culture As Moderating Variables - Muhammad Mursham; Muhammad Asdar; Fauziah Umar (STIE Amkop Makassar, 2022)
Optimal employee performance is the expectation of every State-Owned Enterprise (BUMN). The purpose of this study is to find out the effect of Work-life Balance, motivation and work environment on the performance of PT Semen Tonasa employees both directly and when moderated by AKHLAK culture. This study uses a quantitative approach which intends to explain the position of the variables studied and the relationship between one variable and another. This study will explain the causal relationship between the variables through hypothesis testing. In this study, the analytical method used is moderating analysis (MRA) using the SPSS program. Based on the descriptions in the previous chapters, it can be concluded that Work-life Balance, Work Motivation and Work Environment partially have a significant positive effect on the performance of PT Semen Tonasa employees. Furthermore, moral culture has not been proven to be able to significantly mediate the relationship between Work-life Balance, Work Motivation and Work Environment on Employee Performance. Keywords: Work-life balance, work motivation, work environment, performance, moral culture